Human Rights, Sexual Orientation and Gender Identity in The Commonwealth - Lennox, Corinne; Waites, Matthew (University of London Press, 2013)
Human rights in relation to sexual orientation and gender identity are at last reaching the heart of global debates. Yet 78 states worldwide continue to criminalise same-sex sexual behaviour, and due to the legal legacies of the British Empire, 42 of these - more than half - are in the Commonwealth of Nations. In recent years many states have seen the emergence of new sexual nationalisms, leading to increased enforcement of colonial sodomy laws against men, new criminalisations of sex between women and discrimination against transgender people. Human Rights, Sexual Orientation and Gender Identity in The Commonwealth: Struggles for Decriminalisation and Change challenges these developments as the first book to focus on experiences of lesbian, gay, bisexual, transgender and intersex (LGBTI) and all non-heterosexual people in the Commonwealth. The volume offers the most internationally extensive analysis to date of the global struggle for decriminalisation of same-sex sexual behaviour and relationships. The book includes: The first quantitative analysis of legal change related to sexual orientation and gender identity across all the Commonwealth.